1997
DOI: 10.1161/01.str.28.8.1624
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Allosteric Modification of Hemoglobin on Brain Oxygen and Infarct Size in a Feline Model of Stroke

Abstract: These results are evidence that allosteric hemoglobin modification is protective to the brain after acute focal ischemia, providing a new opportunity for neuroprotection and raising the possibility of enhancing the protective effect of thrombolysis and ion channel blockade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…Whole-brain radiation therapy (WBRT) is a standard treatment for brain metastases (Zimm et al, 1981;Egawa et al, 1986); however, patients may not achieve maximum benefit from WBRT owing to tumour hypoxia, which decreases radiation sensitivity of solid tumours (Rampling et al, 1994;De Santis et al, 1998). Efaproxiral (Efaproxynt, RSR13) is a synthetic allosteric modifier of haemoglobin (Hb), which binds noncovalently in the central water cavity of the Hb tetramer (Wireko et al, 1991;Safo et al, 2001), thereby reducing the Hb-oxygen (O 2 ) binding affinity to facilitate the release of O 2 from Hb to the tissues (Randad et al, 1991;Khandelwal et al, 1993;Kunert et al, 1996;Watson et al, 1997;Steffen, 1998;Eichelbronner et al, 1999). This pharmacodynamic (PD) effect is measured either as a decrease in standard cutaneous pulse oximetry (SpO 2 ) or as an increase in the partial pressure of O 2 (pO 2 ) to produce 50% saturation of Hb (p50).…”
mentioning
confidence: 99%
“…Whole-brain radiation therapy (WBRT) is a standard treatment for brain metastases (Zimm et al, 1981;Egawa et al, 1986); however, patients may not achieve maximum benefit from WBRT owing to tumour hypoxia, which decreases radiation sensitivity of solid tumours (Rampling et al, 1994;De Santis et al, 1998). Efaproxiral (Efaproxynt, RSR13) is a synthetic allosteric modifier of haemoglobin (Hb), which binds noncovalently in the central water cavity of the Hb tetramer (Wireko et al, 1991;Safo et al, 2001), thereby reducing the Hb-oxygen (O 2 ) binding affinity to facilitate the release of O 2 from Hb to the tissues (Randad et al, 1991;Khandelwal et al, 1993;Kunert et al, 1996;Watson et al, 1997;Steffen, 1998;Eichelbronner et al, 1999). This pharmacodynamic (PD) effect is measured either as a decrease in standard cutaneous pulse oximetry (SpO 2 ) or as an increase in the partial pressure of O 2 (pO 2 ) to produce 50% saturation of Hb (p50).…”
mentioning
confidence: 99%
“…Furthermore, during the extreme hypoxic conditions of cerebral ischemia, others have shown that increasing the P 50 of red cell Hb with an allosteric inhibitor or using liposome-encapsulated Hb with a P 50 of 40 Torr reduces infarct volume from experimental stroke [32][33][34]. On the other hand, the experiments that used recombinant HBOCs with P 50 ranging from 3 to 18 Torr also demonstrated substantial reductions in infarct volume [8,9].…”
Section: Interpretation Of Results With Hboc Possessing Different Oxymentioning
confidence: 99%
“…After tracheal intubation, the lungs were mechanically ventilated (tidal volume ϳ2.5 ml, respiratory rate ϳ60 breaths/min) to maintain normocapnia (37)(38)(39)(40)(41)(42). Surgery was performed with aseptic technique, and all surgical fields were infiltrated with 1% lidocaine.…”
Section: Experiments 2: Effects Of Hypothermia and Rsr13-induced Incrementioning
confidence: 99%
“…Wei et al (38) found decreased cerebral venous blood Hb saturation after treatment with RSR13. Finally, Watson et al (37) found increased brain tissue PO 2 in cats subjected to an ischemic insult when given RSR13. Accordingly, RSR13 can serve as a tool to define the effect of hypothermia-induced P 50 changes on brain damage resulting from a cerebral ischemic insult.…”
mentioning
confidence: 94%